Influence of diets on the number and the duration of instare of Phthorimaea operculella - Carneiro, Maurízia de Fátima; Almeida, Armando Antunes de (Pesquisa Agropecuaria Brasileira, 2014)
The influence of three diets on the development of larvae of Phthorimaea operculella (Zeller, 1873) was studied. The larvae were fed with the leaves of Solanum tuberosum L. cv. Bintje and Nicotiana tabacum L. cv. Burley and cv. Amarelinho'. The larvae used in this experiment were bred in laboratory, and they had been separated in three lots just after the eclosion; each lot was constituted by 110 1st - instar larvae. It was verified the existence of a relationship between the age and mean length of larvae, and also between the age and mean weight of larvae for each diet. Among the parameters used to determine the alimentary preference of the larvae of P. operculella, only the mean length of larvae showed significant differences, suggesting that alimentary diets did not affect the larval development.